“Through and Through” Fluoroscopically Guided Catheter Drainage of Extensive Spinal Epidural Abscess: A Case Report - Tanaviriyachai, Terdpong; Pornsopanakorn, Patchara (Journal of Southeast Asian Orthopaedics, 2022)
Purpose: We aimed to present a case of spondylodiscitis with extensive spinal epidural abscess (SEA) that was successfully treated using a minimally invasive technique supplemented with fluoroscopically guided catheter drainage and systemic antibiotic therapy. Methods: A 58-year-old man presented with severe back pain and high-grade fever. He had progressive radiating pain in the lower extremities, followed by sensory deficits in both the lower limbs. Laboratory investigations revealed leukocytosis and high C-reactive protein levels. Magnetic resonance imaging of the thoracic and lumbar regions revealed an extremely large posterior SEA that extends from T6 to S1. As the patient did not respond to intravenous antibiotics alone, he underwent skipped laminectomies with fluoroscopically guided catheter drainage and irrigation. Results: Escherichia coli were detected in purulent material from the abscess. His clinical symptoms were dramatically and immediately relieved after the procedure. The patient achieved complete neurological recovery after six weeks of antibiotic therapy. Conclusions: We suggest a limited approach to the spine with the use of small radio-opaque catheters, representing an interesting option to effectively drain extensive SEAs with less morbidity than the conventional open extensive surgical drainage.